Pengaruh Pemakaian Lidocaine Terhadap Tingkat Nyeri Pasien Retensi Urin Saat Pemasangan Kateter - A'an Delia Acil; Nur Hamim; Roisah Roisah (Pusat Riset dan Inovasi Nasional, 2023)
Pain is an uncomfortable and highly individualized feeling that others cannot feel. Lidocaine is a drug to relieve pain or has a numbing effect on the body. This study aims to determine the effect of lidocaine use on the pain level of urinary retention patients during catheter insertion in the emergency room of Dr Haryoto Lumajang Hospital. The research design used quasi-experiments with Two Group Post-test design. Accidental sampling was used to determine the number of samples and obtained 30 respondents, every 15 people in the intervention group and control group. The pain was measured using the NRS (Numeric Rating Scale) pain scale. The intervention group was given lidocaine 2% as much as one ampoule mixed with lubricant inserted into the urethra using a syringe. The control group only used lubricant. Statistical tests using the Mann-Whitney U Test. In the intervention group, 11 (73.3%) respondents experienced mild pain, and 4 (26.7%) respondents felt moderate pain. In the control group, 14 (93.3%) respondents experienced moderate pain and 1 (6.7%) respondent felt severe pain. Statistical test with a p-value of 0.000 means that lidocaine use has an effect on the pain level of patients with urine retention during catheter insertion. Taking into account the findings of this study, nursing can play a role in improving patient experience and providing better care during catheter insertion in patients with urine retention.